VD_FINDINFO ML / 2012 / 215 vom 13. September 2012 - VD Tribunal cantonal (2012)
TITRE DE MAINLEVÉE, TRANSACTION JUDICIAIRE, COMMANDEMENT DE PAYER, CRÉANCE | 80 al. 1 LP, 80 al. 2 ch. 1 LP, 81 al. 1 LP